Age-related reduction in anxiety and neural encoding of negative emotional memory - Chaudhary, Shefali; Zhang, Sheng; Chen, Yu; Dominguez, Jacqueline C.; Chao, Herta H.; Li, Chiang-Shan R. (Frontiers in Aging Neuroscience, 2024)
Introduction Older adults experience less anxiety. We examined how memory of negative emotional images varied with age and may reflect age-related differences in anxiety. Methods Fifty-one adults, age 22-80 years, underwent imaging with a memory task where negative and neutral images were displayed pseudo-randomly. They were queried post-scan about the images inter-mixed with an equal number of images never displayed. Sensitivity (d’) and reporting bias (Z-score of false alarm rate; Z[FAR]) were quantified with signal detection theory. Results Age was negatively correlated with both Spielberg State Trait Anxiety Inventory (STAI) state score and d’ (negative – neutral) and positively with Z[FAR] (negative – neutral). However, STAI score and d’ or Z[FAR] (negative – neutral) were not significantly correlated. In whole-brain regression, STAI score was correlated with higher activity of the right middle/superior temporal gyri/temporal parietal junction (MTG/STG/TPJ) for “negative correct – incorrect” – “neutral correct – incorrect” trials. Further, the MTG/STG/TPJ activity (β) was also negatively correlated with age. Mediation analyses supported a complete mediation model of age → less anxiety → less MTG/STG/TPJ β. Discussion Together, the findings demonstrated age-related changes in negative emotional memory and how age-related reduction in anxiety is reflected in diminished temporoparietal cortical activities during encoding of negative emotional memory.